A rationale for schistosomiasis control in elementary schools of the rainforest zone of pernambuco, Brazil. - Tereza C Favre; Ana P B Pereira; Aline F Galvão; Luciana C Zani; Constança S Barbosa; Otávio S Pieri (Public Library of Science (PLoS), 2009)
BACKGROUND: Since its beginning in 1999, the Schistosomiasis Control Program within the Unified Health System (PCE-SUS) has registered a cumulative coverage of just 20% of the population from the Rainforest Zone of Pernambuco (ZMP), northeast Brazil. This jeopardizes the accomplishment of the minimum goal of the Fifty-Fourth World Health Assembly, resolution WHA54.19, of providing treatment for schistosomiasis and soil-transmitted helminthiases (STH) to 75% of school-aged children at risk, which requires attending at least 166,000 residents in the 7-14 age range by year 2010 in that important endemic area. In the present study, secondary demographic and parasitological data from a representative municipality of the ZMP are analyzed to provide evidence that the current, community-based approach to control schistosomiasis and STH is unlikely to attain the WHA-54.19 minimum goal and to suggest that school-based control actions are also needed. METHODOLOGY/PRINCIPAL FINDINGS: Data available on the PCE-SUS activities related to diagnosis and treatment of the population from the study municipality were obtained from the State Secretary of Health of Pernambuco (SES/PE) for 2002-2006, complemented by the Municipal Secretary of Health (SMS) for 2003-2004. Data from a school-based stool survey carried out by the Schistosomiasis Reference Service of the Oswaldo Cruz Foundation (SRE/Fiocruz) in 2004 were used to provide information on infection status variation among school-aged children (7-14 years). According to the SES, from 2004 to 2006, only 2,977 (19.5%) of the estimated 15,288 residents of all ages were examined, of which 396 (13.3%) were positive for Schistosoma mansoni. Among these, only 180 (45.5%) were treated. According to the SMS, of the 1,766 examined in the 2003-2004 population stool survey 570 (32.3%) were children aged 7-14 years. One year later, the SRE/Fiocruz school survey revealed that the infection status among those children remained unchanged at 14%-15% prevalence. By 2006, the school-aged population was estimated at 2,981, of which 2,007 (67.3%) were enrolled as pupils. CONCLUSIONS: It is suggested that in the most troubled municipalities individual diagnosis and treatment should be concentrated in school-aged children rather than the whole population. School-based actions involving teachers and children's families may help the health teams to scale up control actions in order to attain the WHA-54.19 minimum goal. This strategy should involve health and education organs and include both enrolled and non-enrolled children.